The implementation of Basic counseling Technique in Elementary School for Helping the development and Alleviating Students Problems in West Pasaman District Education office - Netrawati, Netrawati; Karneli, Yeni; S., Neviyarni (ISLAMIC COUNSELING: Jurnal Bimbingan Konseling Islam, 2018)
Children Development and Characteristic in elementary school-age are different. Each child is different, Low class students between high class students are different. The students come to school in order to be able to follow the education well. But It will not last forever. The problems that they face come from inability in doing assignment,wish, competition among friends, less motivations to study, less supports from parents and others. Deviant behavior also comes from many forms such as, bothering friend, breaking schools facilities, hard in focusing the attention, often musing, and playing-truant. The puroses of this dedication are : 1) class teachers and subject teachers can make a profgram of leadership and Counseling which is integrated into the lesson with tematic approach. 2) Giving Individual Counseling service to help the development and problems of students in Elementary School. The target of this dedication is subject teachers and class teachers of Elementary school in West Pasaman Regency. The method that is used in this research is Descriptive Quantitative, which describes the real condition. Elementary school teachers have had Basis Counseling skill to help students who have problems at school. 30% of elementary school teachers have had basis counseling skill to help students problems at school, and there are still some elementary school teachers who have low Counseling skill.